Conversion and apostasy in the late Ottoman Empire - Deringil, Selim, 1951- (Cambridge : Cambridge University Press, 2012)
In the nineteenth-century Ottoman Empire traditional religious structures crumbled as the empire itself began to fall apart. The state's answer to schism was regulation and control, administered in the form of a number of edicts in the early part of the century. It is against this background that different religious communities and individuals negotiated survival by converting to Islam when their political interests or their lives were at stake. As the century progressed, however, conversion was no longer sufficient to guarantee citizenship and property rights as the state became increasingly paranoid about its apostates and what it perceived as their'denationalization'. The book tells the story of the struggle between the Ottoman State, the Great Powers and a multitude of evangelical organizations, shedding light on current flash-points in the Arab world and the Balkans, offering alternative perspectives on national and religious identity and the interconnection between the two'--.
Includes bibliographical references and index.
Keywords: Religion and state -- Turkey -- History -- 19th century; Islam and state -- Turkey -- History -- 19th century; Conversion -- Islam -- History -- 19th century; Apostasy -- Islam -- History -- 19th century; Islam -- Turkey -- History -- 19th century; Church history -- 19th century; Turkey -- History -- 19th century; Turkey -- Religion -- 19th century